Preparation, molecular definition, spectroscopic characterization and density functional theory calculations on N'-(4-(3-methyl-3-phenylcyclobutyl)-3-phenylthiazol-2(3H)-ylidene)benzenesulfonohydrazide - Sen, Fatih; Cukurovali, Alaaddin (Taylor & Francis Ltd, 2020)
A new sulfonyl derivative (C26H25N3O2S2), N'-(4-(3-methyl-3-phenylcyclobutyl)-3-phenylthiazol-2(3H)-ylidene)benzenesulfonohydrazide, was prepared from a mixture of benzenesulfonylhydrazide and phenylisothiocyanate in ethanol. The 3 D crystal structure, unit-cell dimensions, space group and crystal system of compound were investigated by single-crystal X-ray diffraction (SCXRD). FT-IR spectrum in solid state was observed in the region 4000-400 cm(-1) and the H-1 and C-13 NMR spectra were recorded in CDCl3 solution. In order to support the experimental results, the molecular geometry, vibrational frequencies, H-1 and C-13 chemical shifts in the ground state have been calculated by using the density functional method (DFT/B3LYP) together with 6-311 G+(d, p) basis set. A good linear correlation between experimental and theoretically predicted structural and spectral parameters was observed (R-2 similar to 0.9).
Keywords: Sulfonyl; cyclobutene; thiazole; DFT; X-ray diffraction